2022
DOI: 10.1002/ejoc.202200941
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium‐Catalyzed Selective Reduction of Heteroallenes Through Hydroboration: Amide/Thioamide/Selenoamide Bond Construction and C=X (X=O, S, Se) Bond Activation**

Abstract: An unprecedented conjugated bis-guanidinate (CBG) stabilized aluminium dihydride, [LAlH 2 ; (L={(ArNH)(ArN)À C=NÀ C=(NAr)(NHAr)}; Ar=2,6-Et 2 -C 6 H 3 )] (I) catalyzed chemoselective hydroboration of heteroallenes such as carbodiimide (CDI)s, isocyanates, isothiocyanates, and isoselenocyanates is reported. A wide range of heteroallenes, including electron-donating and withdrawing groups, experience hydroboration to obtain selectively N-boryl amide, N-borylaminal, and N-boryl methyl amine products. More importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 149 publications
(48 reference statements)
2
23
1
Order By: Relevance
“…In these catalysis reactions, the activity of catalyst 1 in terms of TOF and product yield are better than that of other metal catalysts such as β-diketiminato magnesium, bis­(guanidinate) aluminum and zinc dihydride complexes, , AgSbF 6 , and Co­(acac) 2 (for example, 4m , [Zn]: yield = > 99%, TOF = 4.17 h –1 ; [Al]: yield = > 99%, TOF = 4.17 h –1 ; [Co]: yield = 91%, TOF = 0.95 h –1 ; see Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…In these catalysis reactions, the activity of catalyst 1 in terms of TOF and product yield are better than that of other metal catalysts such as β-diketiminato magnesium, bis­(guanidinate) aluminum and zinc dihydride complexes, , AgSbF 6 , and Co­(acac) 2 (for example, 4m , [Zn]: yield = > 99%, TOF = 4.17 h –1 ; [Al]: yield = > 99%, TOF = 4.17 h –1 ; [Co]: yield = 91%, TOF = 0.95 h –1 ; see Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…11–27 Compared with alkene (CC), alkyne (CC) and nitrile (CN) unsaturated bonds, reports on metal-catalyzed hydroboration of isocyanates are very few. 28–35 In 2021, Nembenna et al . reported that a remarkable conjugated bis-guanidinate supported zinc hydride was employed as an efficient catalyst in the hydroboration of a range of aryl and alkyl isocyanates to afford selectively N -boryl formamide, bis(boryl) hemiaminal and N -boryl methyl amine products, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Compared with alkene (CvC), alkyne (CuC) and nitrile (CuN) unsaturated bonds, reports on metal-catalyzed hydroboration of isocyanates are very few. [28][29][30][31][32][33][34][35] In 2021, Nembenna et al reported that a remarkable conjugated bisguanidinate supported zinc hydride was employed as an efficient catalyst in the hydroboration of a range of aryl and alkyl isocyanates to afford selectively N-boryl formamide, bis (boryl) hemiaminal and N-boryl methyl amine products, respectively. 28 Nevertheless, to the best of our knowledge, there have been only three examples of Mg-catalyzed hydroboration of isocyanates so far.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic carbodiimide hydroboration reactions were first reported in 2016 using magnesium catalysts. [8,9] Since then, catalysts for carbodiimide hydroboration using pinacolborane (HBpin) have been reported from across the periodic table, including transition metal, [10][11][12] main group, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and actinide [28] catalysts. Most carbodiimide hydroboration catalysts operate at elevated temperatures (50-80 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Most carbodiimide hydroboration catalysts operate at elevated temperatures (50-80 °C). [8][9][10][16][17][18][19][20][21][22][23][24]27,28] Exceptions that operate at room temperature include a carbatrane magnesium hydride complex, [14] the 9-borabicyclo[3.3.1]nonane dimer, [15] manganese(II) bis(hexamethyldisilazide), [11] a boron-functionalized heptaphosphide Zintl cluster, [25] 9,10-dihydro-9,10-diboraanthracene dianions, [26] and an N-heterocyclic carbene-supported copper alkoxide complex. [12] Initial studies of catalytic isocyanate hydroboration reactions in 2016 and 2017 reported magnesium catalysts for the dihydroboration of isocyanates to form N,O-bis(boryl) hemiaminal products or hydrodeoxygenation reactions to generate N-methyl amines.…”
Section: Introductionmentioning
confidence: 99%